ANALISIS KINERJA DOSEN JURUSAN MATEMATIKA FMIPA UNUD DENGAN METODE CHERNOFF FACES - ARNA PUTRI, GUSTI AYU MADE; NILA KENCANA, I PUTU EKA; SUKARSA, KOMANG GDE (E-Jurnal Matematika, 2012)
This research aims at analyzing work performance of lectures in Math Department Faculty of Science UNUD by using Chernoff faces method. Chernoff faces method was initiated for the first time by Herman Chernoff in 1973 , that is visualization technique in the form of graphic method which presents data with many variables in cartoon face model. This method showsmultivariant data in the shape of human face with position of eyes, nose, ears and mouth which shows the value of variable in different shape, size, position and direction. Since it uses face as research object, in this research  the writer combined Chernoff faces method with physiognomy method. Physiognomy method is science that studies about face characteristic which depicts someone’s personal quality and character. Based on the combination of both methods, it is obtained the result of analysis taken from 80 questioners with 9 variables for students of Math Department Faculty of Science UNUD. It is concluded that work performance of lectures in Math Department Faculty of Science UNUD has been good.
Keywords: Lecture performance; Physiognomy; Chernoff Faces